Neutrophil Survival Signaling During Francisella tularensis Infection - Kinkead, Lauren C.; Krysa, Samantha J.; Allen, Lee-Ann H. (Frontiers in Cellular and Infection Microbiology, 2022)
Neutrophils are the most abundant and shortest-lived leukocytes in humans. Tight regulation of neutrophil turnover via constitutive apoptosis is essential for control of infection and resolution of inflammation. Aberrant neutrophil turnover is hallmark of many disease states. We have shown in previous work that the intracellular bacterial pathogen Francisella tularensis markedly prolongs human neutrophil lifespan. This is achieved, in part, by changes in neutrophil gene expression. Still unknown is the contribution of major neutrophil pro-survival signaling cascades to this process. The objective of this study was to interrogate the contributions of ERK and p38 MAP kinase, Class I phosphoinositide 3-kinases (PI3K), AKT, and NF-B to neutrophil survival in our system. We demonstrate that both ERK2 and p38 were activated in F. tularensis-infected neutrophils, but only p38 MAPK was required for delayed apoptosis, and the rate of cell death in the absence of infection was unchanged. Apoptosis of both infected and uninfected neutrophils was markedly accelerated by the pan-PI3K inhibitor LY2094002, but AKT phosphorylation was not induced, and neutrophil death was not enhanced by AKT inhibitors. In addition, isoform specific and selective inhibitors revealed a unique role for PI3K in neutrophil survival after infection, whereas only simultaneous inhibition of PI3K and PI3k accelerated death of the uninfected controls. Finally, we show that inhibition of NF-B triggered rapid death of neutrophil after infection. Thus, we defined roles for p38, PI3K and NF-kB delayed apoptosis of F. tularensis-infected cells and advanced understanding of Class IA PI3K isoform activity in human neutrophil survival.